HUBUNGAN SINDROM KORONER AKUT DENGAN MORTALITAS PASIEN CORONAVIRUS DISEASE 2019 DI RSPAD GATOT SOEBROTO TAHUN 2020-2021 - Ravena Hasna Haniyah, (2022)
The COVID-19 mortality rate in Indonesia has exceeded the global average by 3.24% on 2020-2021. COVID-19 mortality 30-35% influenced by cardiovascular comorbidity with highest case fatality rate (10%) and acute coronary syndrome as its common manifestation. Indonesian treatments of COVID-19 mostly centered in referral hospitals such as Gatot Soebroto Army Central Hospital. There hasn't been research which correlates acute coronary syndrome with COVID-19 mortality. This research aimed to know the relation of acute coronary syndrome with COVID-19 patient's mortality in Gatot Soebroto Army Central Hospital on 2020-2021. This research was cross sectional with convenient sampling technique. The secondary data of 105 COVID-19 patients shows that 19 were with acute coronary syndrome (18,1%) and 86 were without acute coronary syndrome (81,9%). The result of bivariate analysis using Chi square test shows that there is a significant relation between acute coronary syndrome with COVID-19 patient's mortality (p=0,008; OR=5,854; 95% CI=1,589-21,558). The result of multivariate analysis using logistic regression test shows that there is influence of acute coronary syndrome and sex towards COVID-19 patient's mortality where acute coronary syndrome has the greater influence than sex (p=0,029 and 0,042; OR=4,499 and 2,467; 95% CI=1,169-17,318 and 1,034-5,887). Thus, this research proves that acute coronary syndrome incidence and (male) sex have influence on increasing risk of death in COVID-19 by almost 4.5 and 2.5 times, respectively. Inflammation in COVID-19 as well as sex related genetic, immunity, and psychosocial factors trigger mechanism series which cause acute coronary syndrome and various complications to death.